(untitled) (Journal of Universal Science Research, 2026)
This article discusses the role of community in improving social and communicative competence in preschool education through bilingualism, teaching children to communicate in a second language through daily activities and games, as well as the issue of language acquisition in a natural environment through poems, stories, and songs, and the development of childrenʼs problem-solving, collaboration, and creative thinking skills for cognitive and social development